Efficacy of nasal continuous positive airway pressure therapy in chronic heart failure: importance of underlying cardiac rhythm. Issue 11 (1st November 1998) - Kiely, John L; Deegan, Paul; Buckley, Aidan; Shiels, Paul; Maurer, Brian; McNicholas, Walter T
Abstract : BACKGROUND: Some previous reports have indicated beneficial cardiac effects of nasal continuous positive airway pressure (NCPAP) in patients with severe congestive heart failure (CHF), but others have reported deleterious cardiac effects, particularly among patients in atrial fibrillation (AF). The aim of this study was to determine if differences in cardiac rhythm influence the acute cardiac response to NCPAP. METHODS: Eleven consecutive patients with CHF were recruited, six in atrial fibrillation (AF) and five with sinus rhythm (SR). Cardiac index was measured during awake NCPAP application by the thermodilution technique during cardiac catheterisation. NCPAP was applied in a randomised sequence at pressures of 0, 5, and 10 cm H2 O with three 30 minute applications separated by 20 minute recovery periods without NCPAP. RESULTS: Significant differences were found between the AF and SR groups for cardiac index responses to NCPAP (p = 0.004, ANOVA) with a fall in cardiac index in the AF group (p = 0.02) and a trend towards an increase in the SR group (p = 0.10). Similar differences were seen between the groups in stroke volume index responses but not in heart rate responses. Changes in systemic vascular resistance were also significantly different between the two groups (p< 0.005, ANOVA), rising in the AF group but falling in the SR group. CONCLUSIONS: These data indicate an important effect of underlying cardiac rhythm on the awake haemodynamic effects of NCPAP in patients with CHF.